Predicting post-war US recessions: a probit modelling approach - Alexiou, Constantinos; Trachanas, Emmanouil (Elsevier, 2020)
This paper investigates the factors associated with the occurrences of US recessions over the period 1963Q1 to 2018Q2 using multivariate probit models. The evidence suggests that the probability of a recession decreases with higher profitability, as implied by the proponents of the Marxian tradition. Equally significant are the results that relate to manufacturing activity, investment, and inflation. The theoretical argument however, of those who regard the burgeoning growth of private credit as a factor triggering recessions, is not supported by our findings. Finally, interest rates, Tobin's Q, and labour's share of income are not statistically significant, hence implying that the likelihood of these being closely associated with US economic recessions is rather slim.
Keywords: US recessions; Profitability; Probit models